A Comparative Analysis of the Use of GitHub by Librarians and Non-Librarians - Eaton, Mark Edward (Evidence Based Library and Information Practice, 2018)
Objective – GitHub is a popular tool that allows software developers to collaborate and share their code on the web. Librarians have adopted GitHub to support their own work, sharing code in support of their libraries. This paper asks: How does librarians’ use of GitHub compare to that of other users?Methods – To retrieve quantitative data on GitHub users, we queried the GitHub APIs (application programming interfaces). By assembling data on librarians’ use of GitHub, as well as on a comparison group, we provided preliminary comparisons of these two samples. We analyzed and visualized this data across a number of variables to offer salient insights as to how librarians compare to randomly selected GitHub users.Results – Librarians regularly use a more diverse range of programming languages than the comparison group, hinting at a broad range of possible uses of code in libraries. While the librarians’ sample group did not demonstrate statistically significant differences from the comparison group on most measures of activity and popularity, they scored significantly higher in reach and productivity than the comparison group. This could be due to librarians’ greater longevity on GitHub, as well as their greater investment in GitHub as a tool for sharing.Conclusion – Our data suggest that librarians are actively building their libraries with code and sharing the results. While it was unclear whether librarians were more active or popular on GitHub than the comparison group, it was clear that they demonstrated statistically significant outperformance in terms of reach and productivity. To explain these findings, we hypothesized that librarians’ embrace of GitHub is in line with widely held values of “openness” in the library profession.